FRI0124 Increased risk of diastolic heart failure in RA – what should we screening for?. (23rd January 2014) - Schau, T.; Gottwald, M.; Neuss, M.; Ridjab, D.; Fischer, I.; Butter, C.; Zaenker, M.
Abstract : Background: Patients with rheumatoid arthritis (RA) share an increased risk of diastolic heart failure with normal ejection fraction (HFNEF), which is often underrecognized. Age, female gender and history of hypertension are important risk factors. Also, persistant disease activity and disease duration have been shown to be significant contributors. Therefore, effective screening for heart failure should be part of follow-up evaluation in RA-patients. However, not all patients with HFNEF are symptomatic. In contrast, RA-related fatigue and functional impairment may influence symptoms of heart failure and interfere with exercise testing. Objectives: To determine diagnostic value of symptoms, laboratory results, and technical findings for classification of HFNEF in RA-patients. Methods: We analyzed data of our prospective heart failure study of consecutively recruited RA-patients showing up in our community based outpatient-clinic. All patients were interviewed using a standardized questionnaire. Clinical signs were evaluated based upon Framingham criteria. Laboratory tests included NT-proBNP. Echocardiography contained tissue doppler and global longitudinal strain (GLS) imaging. Results: 162 pat., n=110 (68%) female, mean (SD) age 61.3 (±13.1) years, mean disease duration 12.5 (±11.4) years, mean DAS28 2.8 (±1.0) were enrolled. Appropriate echocardiographic data was available in 155 pat. LVEF<50% was found in 6 pat. (3.7%), 3 (2%) pat. had additional symptoms of NYHA class>1 and were classified having systolic heart failure. Of the remaining 149 pat. with normal EF, 62 (41, 6%) had symptoms of NYHA-class>1, and HFNEF according to ESC criteria was finally classified in 31 (21%) pat. In the group with normal EF, hypertension was found in 83 (56%), diabetes in 21 (14%), GFR<60 ml/min in 22 (15%), PAOD in 14 (9%), CAD in 25 (17%), prior MI in 8 (5%), stroke/TIA in 3 (2%) pat. Conclusions: When screening RA-patients, peripheral edema, dyspnea on exertion, nocturia, increased NTproBNP, high grade diastolic dysfunction, and abnormal GLS are main indicators of HFNEF. There is low diagnostic value of other symptoms and clinical findings. Disclosure of Interest: None Declared